THE IMPACT OF TIKTOK ADDICTION ON ACADEMIC PERFORMANCE AMONG UNIVERSITY STUDENTS: ACADEMIC PROCRASTINATION AS A KEY MEDIATOR - Zulfa Irawati; Imam Riefly Aditomo; Yashinta Anisa Sari Ayuningtyas (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
This study investigates the relationship between TikTok addiction and academic performance among university students, with academic procrastination examined as a mediating variable. Grounded in self-escape theory, the research explores how excessive TikTok use may act as a maladaptive coping mechanism that contributes to procrastinatory behaviors, ultimately affecting academic outcomes. This study used a cross-sectional design and data collected from 287 students at Universitas Muhammadiyah Surakarta through an online questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that TikTok addiction has no significant direct effect on academic performance. However, it significantly increases academic procrastination, which in turn negatively affects academic performance. The mediation analysis confirmed that academic procrastination plays a key intermediary role in the relationship between TikTok use and academic success.